The Influence of Financial Ratios and Non-Accounting Information on Credit Decisions at Bank Syariah Indonesia (BSI) - Edy Zulfiar; Faisal Faisal; Mariana Mariana; Anhar Firdaus; Diana Diana (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
This quantitative causal-associative study investigates the influence of financial ratios—i.e., Fixed Assets Turnover (FATO), Return on Net Worth (RONW), and Debt-to-Equity Ratio (DER)—and non-accounting information on credit decisions at Bank Syariah Indonesia (BSI) in Pidie Regency, Aceh, during 2023–2024. Using a census, data were collected from 359 credit recipients, combining secondary financial reports and internal credit documentation. Multiple linear regression and path analysis were performed to examine both the direct and mediating effects of the research variables. The results show that FATO (β = 0.478, p < 0.001) and RONW (β = 0.174, p < 0.001) positively impact credit decisions, whereas the influence of DER (β = 0.028, p = 0.279) is not significant. Meanwhile, non-accounting information (β = 0.154, p = 0.013) both directly affects credit decisions and mediates the relationship between financial ratios and lending outcomes, increasing the explanatory power by 1.2% (ΔR² = 0.012). These findings indicate that qualitative factors, such as managerial integrity, borrower reputation, and business environment, enhance the assessment of creditworthiness. This study contributes to Islamic banking practices by integrating financial and non-financial indicators, providing a more holistic approach for evaluating credit risk and supporting accurate, fair, and sustainable credit decisions.